Genetic Environments of the rmtA Gene in Pseudomonas aeruginosa Clinical Isolates - Yamane, Kunikazu (American Society for Microbiology, 2004)
Nine Pseudomonas aeruginosa strains showing very high levels of resistance to various aminoglycosides have been isolated from clinical specimens in seven separate Japanese hospitals in five prefectures since 1997. These strains harbor the newly identified 16S rRNA methylase gene (rmtA). When an rmtA gene probe was hybridized with genomic DNAs of the nine strains digested with EcoRI, two distinct patterns were observed. The 11.1- and 15.8-kb regions containing the rmtA genes of strains AR-2 and AR-11, respectively, were sequenced and compared. In strain AR-2, a transposase gene-like sequence (sequence 1) and a probable tRNA ribosyltransferase gene (orfA) were located upstream of rmtA, and a Na(+)/H(+) antiporter gene-like sequence (sequence 2) was identified downstream of rmtA. This 6.2-kbp insert (the rmtA locus) was flanked by 262-bp κγ elements. Part of the orfQ gene adjacent to an inverted repeat was found outside of the rmtA locus. In strain AR-11, the rmtA gene and sequence 2 were found, but the 5′ end of the orfA gene was truncated and replaced with IS6100. An orfQ-orfI region was present on each side of the rmtA gene in strain AR-11. The G+C content of the rmtA gene was about 55%, and since the newly identified rmtA gene may well be mediated by some mobile genetic elements such as Tn5041, further dissemination of the rmtA gene could become an actual clinical problem in the near future.